Pengaruh Green Accounting, Corporate Social Responsibility Dan Carbon Emission Disclosure Terhadap Nilai Perusahaan - Sakina, Ameylia Geulis; Qintharah, Yuha Nadhirah; Chairunnisa, Nurlaila Maysaroh; Putra, Purnama; Risa, Nurma (Universitas Serang Raya, 2024)
This study aims to determine the effect of Corporate Social Responsibility, Environmental Disclosure and Profitability on Firm Value.This study uses quantitative methods and the type of data used is secondary data in the form of company financial reports. The population used in this study are consumer non-cylicals sector companies in the food & beverage sub-sector listed on the Indonesia Stock Exchange for the period 2018-2022. The samples to be used in this study were selected based on purposive sampling method, so that a total of 105 samples were obtained from 21 companies in the consumer non-cylicals sector of the food & beverage sub-sector during the 2018-2022 period. The data in this study were processed using the SSPS (Statistical Product and Service Solution) version 23 program.The results of this study indicate that Corporate Social Responsibility has a negative and significant effect on Firm Value, Environmental Disclosure has a positive effect on Firm Value, Profitability with ROE proxy cannot moderate the relationship between Corporate Social Responsibility on Firm Value, Profitability with ROE proxy weakens the relationship between Environmental Disclosure on Firm Value.